Student Teachers' Classroom Impact during Their Practicum in the Times of the Pandemic - Laura Alonso-Díaz; Gemma Delicado-Puerto; Francisco Ramos; Cristina Manchado-Nieto (MDPI AG, 2023)
The COVID-19 pandemic impacted societal structures worldwide. In the educational realm, the forced closure, and subsequent reopening of school settings disrupted the personal and professional lives of administrators, teachers, parents, and students. Two groups of Spanish stakeholders affected by the return to face-to-face instruction during the pandemic were the University of Extremadura's student teachers and their mentors during the practicum, as student teaching is known in Spain. This study investigated 28 student teachers' and 26 mentors' responses to a questionnaire enquiring on the main challenges resulting from the pandemic, as well as student teachers' contributions to the classroom during this difficult time. Cualitative software was used to analyze participants' responses allowed us to identify four main themes: attitudes; classroom management issues; adaptations and restrictions; and academic-experiential modifications. Overall, the findings revealed student teachers' and mentors' positive opinions about their joint work experience and about student teachers' logistical and technological support.